Forests, trees and human health - Nilsson, Kjell; Nilsson, Kjell; SpringerLink (Online service). (New York Springer, 2011)
The link between modern lifestyles and increasing levels of chronic heart disease, obesity, stress and poor mental health is a concern across the world. The cost of dealing with these conditions places a large burden on national public health budgets so that policymakers are increasingly looking at prevention as a cost-effective alternative to medical treatment. Attention is turning towards interactions between the environment and lifestyles. Exploring the relationships between health, natural environments in general, and forests in particular, this groundbreaking book is the outcome of the Eu.
Chapter 1: Forests, Trees and Human Health and Well-being: Introduction; Chapter 2: Urban Forests and Their Ecosystem Services in Relation to Human Health; Chapter 3: Forest Products with Health-Promoting and Medicinal Properties; Chapter 4: Negative Aspects and Hazardous Effects of Forest Environment on Human Health; Chapter 5: Health Benefits of Nature Experience: Psychological, Social and Cultural Processes; Chapter 6: Health Benefits of Nature Experience:The Challenge of Linking Practice and Research; Chapter 7: Health Benefits of Nature Experience: Implications of Practice for Research.
Includes bibliographical references and index.
Keywords: Electronic books